Post wall, post square : how Bush, Gorbachev, Kohl, and Deng shaped the world after 1989 - Spohr, Kristina (Yale University Press, 2020)
A landmark global history that makes us rethink how the Cold War ended and our present era was born This book offers a bold new interpretation of the revolutions of 1989, showing how a new world order was forged--without major conflict. Based on extensive archival research, Kristina Spohr attributes this in large measure to determined diplomacy by a handful of international leaders, who engaged in tough but cooperative negotiation to reinvent the institutions of the Cold War. She offers a major reappraisal of George H. W. Bush and innovative assessments of Mikhail Gorbachev and Helmut Kohl, as well as Margaret Thatcher and François Mitterrand. But, she argues, Europe's transformation must be understood in global context. By contrasting events in Berlin and Moscow with the brutal suppression of the pro-democracy movement in Beijing, the book reveals how Deng Xiaoping pushed through China's very different Communist reinvention. Here is an authoritative yet highly readable exploration of the crucial hinge years of 1989-1992 and their consequences for today's world